2003
DOI: 10.1016/s0885-3924(03)00043-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Progression of Advanced “Hormone-Resistant” Prostate Cancer During Palliative Treatment with Progestins for Cancer Cachexia

Abstract: We report three patients with advanced "hormone-resistant" prostate cancer, each of whom had rapid progression of the disease during treatment with megestrol acetate for cancer cachexia. All patients had been previously treated with total androgenic deprivation. With progression of the disease, megestrol acetate was given to palliate the cancer-related wasting syndrome. No other antineoplastic drugs were contemporaneously given, and no concomitant condition that could favor the progression of the disease was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Megestrol acetate is commonly utilized for the treatment of hot flashes in men receiving ADT and has been reported to reduce hot flashes by up to 85% [50]. A few case reports describe progression of prostate cancer with megestrol acetate; therefore, monitoring of disease is important [51,52]. Depot medroxyprogesterone acetate (MPA) has been studied as an intervention to reduce hot flashes in men on ADT.…”
Section: Management Of Adt Effects On Neuroendocrine and Neuropsycmentioning
confidence: 99%
“…Megestrol acetate is commonly utilized for the treatment of hot flashes in men receiving ADT and has been reported to reduce hot flashes by up to 85% [50]. A few case reports describe progression of prostate cancer with megestrol acetate; therefore, monitoring of disease is important [51,52]. Depot medroxyprogesterone acetate (MPA) has been studied as an intervention to reduce hot flashes in men on ADT.…”
Section: Management Of Adt Effects On Neuroendocrine and Neuropsycmentioning
confidence: 99%
“…Tassinari et al also reported the cases of three patients with advanced "hormone-resistant" prostate cancer, each of whom had rapid disease progression during their treatment with MA for cancer-associated cachexia. However, when MA was discontinued for inefficacy reasons, serum PSA values quickly stopped increasing, bone pain decreased, and patient performance status improved (19). Although it was not case regarding the administration of MA in patients with CRPC, one case report showed that patients with prostate cancer who were given MA for symptomatic relief of hot flashes after administration of a luteinizing hormone-releasing hormone analog, experienced a PSA value which declined more than 60% when MA therapy was stopped (25).…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that mutation in the steroid binding domain of the androgen receptor was found in the human prostatic carcinoma cell line or in tissue from men with advanced prostate cancer (18). In this context, three case reports showed rapid progression of advanced CRPC during palliative treatment with MA for cancer cachexia (19). Therefore, MA might induce the proliferation of CRPC via the mutated androgen receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the inclusion of patients still receiving antineoplastic treatment and/or those who have relatively short follow-up can underestimate treatment-associated morbidity and the potentially harmful consequences of a hormonal treatment even in this setting. 4 However, in well-designed studies, the superiority of high-dose progestins compared to placebo is clearly demonstrated, 5 and was the main reason to include one of these drugs (medroxyprogesterone acetate) in our trial.…”
Section: Authors' Responsementioning
confidence: 92%